2018
DOI: 10.1002/rth2.12074
|View full text |Cite
|
Sign up to set email alerts
|

Update on the electrolytic IVC model for pre‐clinical studies of venous thrombosis

Abstract: Essentials Three key updates are provided on the electrolytic inferior vena cava model (EIM).The originally described stimulator equipment has been discontinued; we developed an alternative.The fibrinolytic system and the current and time dependency of the EIM was characterized.EIM allows the investigation of the fibrinolytic system, critical for endovascular therapies. BackgroundThe electrolytic inferior vena cava model (EIM) is a murine venous thrombosis (VT) model that produces a non‐occlusive thrombus. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…A thrombus develops quickly in the direction of the blood flow and thrombus sizes are highly consistent. This venous thrombosis model is used to study pro-thrombotic, anti-thrombotic, and thrombolytic therapies (28)(29)(30). Moreover, this model can mimic the early and late stages of venous thrombosis.…”
Section: Electrolytic Inferior Vena Cava Thrombosis Modelmentioning
confidence: 99%
“…A thrombus develops quickly in the direction of the blood flow and thrombus sizes are highly consistent. This venous thrombosis model is used to study pro-thrombotic, anti-thrombotic, and thrombolytic therapies (28)(29)(30). Moreover, this model can mimic the early and late stages of venous thrombosis.…”
Section: Electrolytic Inferior Vena Cava Thrombosis Modelmentioning
confidence: 99%
“…Recently the EIM application was expanded for the study of pro‐thrombotic conditions . Further, imaging studies recently demonstrated the consistent thrombus size is both current and time dependent, enabling researchers to modify these parameters to create thrombi of consistent size to study both pro‐thrombotic and anti‐thrombotic phenotypes, supporting the modification introduced in 2015. Additionally, a new approach was recently introduced to address lack of equipment availability and high cost, following the same principles but significantly reducing equipment cost .…”
Section: Mouse Models Of Venous Thrombosismentioning
confidence: 99%
“…In contrast, stimulation of the fibrinolytic system could be a safer option for thrombosis treatment because the coagulation system will be unaffected, and PAI-1 is considered a potential therapeutic target in VT (24, 34 -36). For these studies, VT was induced via the electrolytic inferior vena cava model (EIM) as described (37). After induction, mice received either 3 mg/kg MDI-2268, or low-molecular weight heparin (LMWH), or vehicle alone three times/day by IP injection.…”
Section: Medicinal Chemistry and Structure-activity Relationship (Sarmentioning
confidence: 99%
“…The EIM is a murine model of venous thrombosis that has been described previously (37). Briefly, thrombosis is induced under flow conditions by a small current run through a copper wire applied to the anterior vein wall.…”
Section: Murine Model Of Venous Thrombosismentioning
confidence: 99%
See 1 more Smart Citation